A novel independent harmonic tuned two‐port output network for efficiency enhanced RF power amplifiers. Issue 2 (7th September 2020) - Banerjee, Deepayan; Saxena, Antra; Hashmi, Mohammad
Abstract: This article introduces a simple two‐port harmonic tuned output network‐based design of RF Power Amplifiers. The proposed output network facilitates mutual independence between the fundamental, second, and third harmonic impedances, which thereby eases the tuning process. The proposed two‐port harmonic tuning network has been synthesized, fabricated, and measured separately to demonstrate the harmonic independence behavior. Thorough graphical and analytical deductions are provided for the design scheme. The proposed design strategy has been validated with a Cree 10 W GaN HEMT based fabricated prototype at 2.4 GHz. The measured results show an obtained drain efficiency up to 82.3% and a gain of > 11.0 dB.